Retrospective analysis of the clinical efficacy of minocycline regimen in the radical treatment of helicobacter pylori and its adverse reactions - Wenjun Zhao; Nailing Liu; Yanan Yu; Lin Yang (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the clinical effect of minocycline regimen in the radical handling of helicobacter pylori and its adverse reactions. Method: The meta-analysis was conducted from February to April 2024, and comprised literature search on Chinese Biomedical, Wanfang, VIP, China National Knowledge Infrastructure, Cochrane Library, ScienceDirect, EMBASE and PubMed databases for case-control studies published between January 2010 and December 2022 in which the minocycline regimen had been employed to eradicate helicobacter pylori. Two researchers retrieved the data independently, and they evaluated each study’s risk of bias using the Cochrane Handbook 5.3. Data was subjected to meta-analysis using RevMan 5.3. Results: Of the 761 studies initially identified, 281(37%) were assessed for eligibility, and 6(2.13%) of them were analysed in detail that had an overall sample of 1,650 patients; 822(49.7%) cases and 828(50%) controls. The radical treatment rate among the cases (692[84.18%]) was higher than that in the control group (678[81.88%]) (p=0.88). The incidence of adverse reactions in the two groups was not significantly different (p=0.14). Conclusion: Minocycline was found to have a definite therapeutic effect on helicobacter pylori. Kewords: Minocycline, Helicobacter pylori, Clearance rate, Incidence of adverse reactions.